Hydrogen Loss on Venus Driven by Photochemistry - Hao Gu; Jun Cui; Xiaoshu Wu; Xu Huang; Shiqi Wu; Wenlong Li; Jinjin Zhao; Haoyu Lu; Lei Li (The Astrophysical Journal Letters)
Venus has experienced substantial H loss through hydrodynamic outflow in its early history, transforming from a warm and wet state to the current arid and scorching state. While Venus continues to lose H today, no consensus has been reached regarding the present dominant escape mechanisms. Recently, photochemical escape via HCO ^+ dissociative recombination (DR) has been proposed as a prevailing process that had previously been overlooked. However, due to uncertainties in the underlying H _2 abundance and the solar cycle variations of the input radiative energy, it is essential to explore how these factors influence the modeled H escape flux under different conditions. By combining a photochemical model with a Monte Carlo test particle model, we demonstrate that the H escape flux increases with the underlying H _2 concentration over a possible range of 1 × 10 ^6 –2 × 10 ^8 cm ^−2 s ^−1 , but varies nonmonotonically with solar activity due to the competition between photochemical production and collisional hindrance. While our results confirm the dominant role of HCO ^+ DR, we find that the ion-neutral reaction ${OH}^{+}+{\rm{O}}→ {{\rm{O}}}_{2}^{+}+{\rm{H}}$ makes an additional contribution, which could reach more than 30% of total H escape. Our findings provide valuable insights into the foundational understanding of photochemically driven H escape because the same mechanism should function in a much broader context.